Abstract 163: Total Spinal Cord Infarction, An Underrecognized Postoperative Complication - Hamza M. Ahmed; Jonathan L. Garcia‐Ramiu; Raman V. Singh; Ahmad Al‐Awwad (Stroke: Vascular and Interventional Neurology)
Introduction Spinal cord infarctions (SCI) are scarce entities, constituting only 0.3‐1% of all strokes, with complete or posterior spinal cord involvement detailed in the case below being even rarer. Often caused by sudden interruption of blood flow to the spinal cord due to embolic phenomena, intrinsic factors such as connective tissue disease, and due to intra/post‐operative hypotension leading to ischemia or infarction. The resultant acute spinal cord dysfunction manifests as; motor weakness, loss of senses of pain and temperature, altered proprioception, bowel and bladder dysfunction Spinal blood supply comprises of the anterior spinal artery (ASA) and the two posterior spinal arteries, with supply to the spinal arteries being derived from various regional arteries: C1‐T3 is supplied by the vertebral arteries, T3‐T7 is served by a branch from the intercostal arteries, and the Adamkiewicz artery supplies T8 to the medullary conus. The thoracolumbar level is primarily supplied by only a small number of radicular arteries, originating from segmental branches of the aorta, specifically the posterior intercostal and lumbar branches, which extend towards the intervertebral foramina where they split into the anterior and posterior radicular arteries. The largest radicular artery, commonly referred to as the arteria radicularis magna of Adamkiewicz (or main anterior radicular artery), typically arises on the left between T9 and T12, but may be located on the right or emerge anywhere from T5 to L4 in approximately 17% of cases. This extensive segment of the spinal cord only is typically supplied by only two or three small radicular branches, occuring between the lower cervical and mid‐to‐lower thoracic levels, making it a watershed zone. Methods Case report and literature review Results 73‐year‐old woman with history of hypertension, long‐term smoking, extensive peripheral vascular disease, R lung cancer (in remission after 3 rounds of radiation, and newly diagnosed calcified heterogeneous left renal mass concerning for malignancy status‐post right femoral access with embolization of left lumbar arteries at the level of L1‐L3 with 800 micrometer particles and tungsten‐platinum coils on 12/19/22), transferred from a surgical center on 12/21/22 for post‐operative paraparesis (R›L), paresthesia , urinary retention, and constipation initially thought to be post‐anesthetic effects. MRI T and L spine with and without contrast demonstrated diffusion restriction from the level of T10 to the conus suggestive of anterior and posterior spinal cord infarct, thought to be in the setting of recent embolization with extensive atherosclerotic burden. Neurological exam significant for lower extremity paraparesis ( R 2/5 , L 3/5) with T10 sensory level to pin‐prick and temperature, hyporeflexia, and absent proprioception in bilateral lower extremities. Full dose aspirin and high intensity statin was started with patient managed conservatively due to presentation outside window for thrombolysis. Conclusion Spinal cord infarcts typically present with motor weakness due to ASA occlusion however, sensory level and proprioceptive loss as accompanying factors are important considerations to rule in total cord (anterior + posterior) infarcts, especially in post‐op patients undergoing thoraco‐lumbar access/embolization as earlier recognition may make them eligible for treatments such as thrombolysis.